Clovis Paleoecology and Lithic Technology in the Central Rio Grande Rift Region, New Mexico. Issue 2 (20th April 2013) - Hamilton, Marcus J.; Buchanan, Briggs; Huckell, Bruce B.; Holliday, Vance T.; Shackley, M. Steven; Hill, Matthew E.
Abstract: Clovis sites occur throughout the southwestern United States and northwestern Mexico, but are poorly documented in the central Rio Grande rift region. Here, we present data from two relatively unknown Clovis projectile point assemblages from this region: the first is from the Mockingbird Gap Clovis site and the second is from a survey of the surrounding region. Our goals are to reconstruct general features of the paleoecological adaptation of Clovis populations in the region using raw material sourcing and then to compare the point technology in the region to other Clovis assemblages in the Southwest and across the continent. Our results show that both assemblages were manufactured from similar suites of raw materials that come almost exclusively from the central Rio Grande rift region and the adjacent mountains of New Mexico. Additionally, we show that Clovis projectile points in the study region are significantly smaller than the continental average. Our results suggest that Clovis populations in this region operated within a large, well-known, and relatively high-elevation territory encompassing much of northern and western New Mexico.